2022
DOI: 10.48550/arxiv.2201.12171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling Active Non-Markovian Oscillations

Abstract: Modelling noisy oscillations of active systems is one of the current challenges in physics and biology. Because the physical mechanisms of such processes are often difficult to identify, we propose a linear stochastic model driven by a non-Markovian bistable noise that is capable of generating self-sustained periodic oscillation. We derive analytical predictions for most relevant dynamical and thermodynamic properties of the model. This minimal model turns out to describe accurately bistable-like oscillatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…We estimated that an oscillating hair bundle generates at least 5 aW or 146 k B T /cycle. This value is in good agreement with a recent estimate of 100 k B T /cycle, based on a model fitted to bi-stable oscillations of hair bundles [24]. Furthermore, we derived a scaling behavior, indicating that the energy dissipation per cycle scaled by k B T • s is of the same order of magnitude as the characteristic frequency.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We estimated that an oscillating hair bundle generates at least 5 aW or 146 k B T /cycle. This value is in good agreement with a recent estimate of 100 k B T /cycle, based on a model fitted to bi-stable oscillations of hair bundles [24]. Furthermore, we derived a scaling behavior, indicating that the energy dissipation per cycle scaled by k B T • s is of the same order of magnitude as the characteristic frequency.…”
Section: Discussionsupporting
confidence: 91%
“…Although these studies answered the question of whether these spontaneous movements were active or passive, they did not investigate the nonequilibrium energetics of the driving. Investigators have subsequently used a combination of modeling and single-cell data analysis to estimate the energy that is dissipated during an oscillatory cycle [23, 24]. These studies relied on the observed displacement of the bundle without perturbing it.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, when the distribution p(x t ) is unimodal (corresponding to the case of fast relaxation times t κ ) the learning performance worsens as the data is not su ciently informative about the latent state C. Interestingly, we observe that along the "phase boundary" between unimodal and bimodal the error is roughly homogeneous and approximately equal to 25%. The presence of two "phases" in terms of the bimodality/unimodality of the distribution p(x t ) is rationalised using recent analytical results [33] for the loci of the phase boundary in the the case k = 1, which is given by…”
Section: The Performance Of Auto-regressive Modelsmentioning
confidence: 97%
“…We rst describe a latent variable model for seq2seq tasks, which we call the Stochastic Switching-Ornstein-Uhlenbeck (SSOU) model. This model was introduced recently in biophysics [33] to describe the spontaneous oscillations of the tip of hair-cell bundles in the ear of the bullfrog. We consider observable sequences X = (X t ) which are described by a one-dimensional stochastic process whose dynamics is driven by an autonomous latent stochastic process C = (C t ) and a Gaussian white noise that is independent to C t .…”
Section: A Model For Sequence-to-sequence Tasksmentioning
confidence: 99%
See 1 more Smart Citation